p53 Pre- and Post-Binding Event Theories Revisited: Stresses Reveal Specific and Dynamic p53-Binding Patterns on the p21 Gene Promoter - Millau, Jean-François; Bastien, Nathalie; Bouchard, Éric F.; Drouin, Régen (Cancer research (Chicago, Ill.), 2009)
p53 is a master transcription factor that prevents neoplasia and genomic instability. It is an important target for anticancer drug design. Understanding the molecular mechanisms behind its transcriptional activities in normal cells is a prerequisite to further understand the deregulation effected by mutant p53 in cancerous cells. Currently, how p53 coordinates transcription programs in response to stress remains unclear. One theory proposes that stresses induce pre-binding events that direct p53 to bind to specific response elements, whereas a second posits that, in response to stress, p53 binds most response elements and post-binding events then regulate transcription initiation. It is critical to establish the relevance of both theories and investigate whether stresses induce specific p53-binding patterns correlated with effector gene induction. Using unique in cellulo genomic footprinting experiments, we studied p53 binding to the five response elements of p21 in response to stresses and monitored p21 mRNA variant transcription. We show clear footprints of p53 bound to response elements in living cells and reveal that the binding of p53 to response elements is transient, subject to dynamic changes during stress responses, and influenced by response element pentamer orientations. We show further that stresses lead to specific p53-binding patterns correlated with particular p21 mRNA variant transcription profiles and that p53 binding is necessary but not sufficient to induce p21 transcription. Our results indicate that pre- and post-binding events act together to regulate adapted stress responses; this paves the way to the unification of pre- and post-binding event theories. [Cancer Res 2009;69(21):8463–71]